2023
DOI: 10.1186/s12967-023-04461-4
|View full text |Cite
|
Sign up to set email alerts
|

FTO-targeted siRNA delivery by MSC-derived exosomes synergistically alleviates dopaminergic neuronal death in Parkinson's disease via m6A-dependent regulation of ATM mRNA

Yan Geng,
Xinyi Long,
Yuting Zhang
et al.

Abstract: Background Parkinson's disease (PD), characterized by the progressive loss of dopaminergic neurons in the substantia nigra and striatum of brain, seriously threatens human health, and is still lack of effective treatment. Dysregulation of N6-methyladenosine (m6A) modification has been implicated in PD pathogenesis. However, how m6A modification regulates dopaminergic neuronal death in PD remains elusive. Mesenchymal stem cell-derived exosomes (MSC-Exo) have been shown to be effective for treati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“… 136 , 137 Angelova et al discovered that α-syn oligomers can bind to cell membranes and induce ferroptosis by driving lipid peroxidation. 40 Furthermore, research findings indicate that α-syn plays a role in metabolizing essential membrane PUFAs like arachidonic acid (AA), 6 , 138 including increasing its membrane fluidity and regulating vesicle assembly and synaptic transmission. 109 , 138 , 139 A recent study utilizing transmission electron microscopy (TEM) and optical microscopy imaging technologies suggested that the immunoreactivity of α-syn in LB is closely linked to high levels of membrane lipids, fragmented organelles, and vesicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 136 , 137 Angelova et al discovered that α-syn oligomers can bind to cell membranes and induce ferroptosis by driving lipid peroxidation. 40 Furthermore, research findings indicate that α-syn plays a role in metabolizing essential membrane PUFAs like arachidonic acid (AA), 6 , 138 including increasing its membrane fluidity and regulating vesicle assembly and synaptic transmission. 109 , 138 , 139 A recent study utilizing transmission electron microscopy (TEM) and optical microscopy imaging technologies suggested that the immunoreactivity of α-syn in LB is closely linked to high levels of membrane lipids, fragmented organelles, and vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…The gradual degeneration of dopaminergic neurons in the substantia nigra (SN), along with abnormally aggregated α-synuclein (α-syn) forming Lewy bodies, are the pathological hallmarks of PD. 6 Although the current dopamine-based pharmacological therapies can alleviate motor symptoms in early-stage patients, there is a lack of effective neuroprotective treatment methods to prevent PD from progressively deteriorating. Therefore, investigating the underlying mechanisms of PD to explore novel targets and develop the next generation of therapies is urgently needed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, miRNA-enriched EVs have been shown to exert neuroprotective effects, with miR-29 and miR-22 variants downregulating pathological Aβ production and inflammatory cascades in AD models [156,157]. Additionally, m6A modifications in RNA processes, implicated in PD, have been targeted using MSC-EVs to deliver demethylase FTO-targeted siRNAs, demonstrating neuroprotective outcomes [158].…”
Section: The Future Of Drug Delivery: Evs In the Clinical Settingmentioning
confidence: 99%
“…They suggested that FTO affects ATM expression by influencing the stability of ATM mRNA in dopaminergic neurons. FTO knockdown inhibited ATM expression, suppressing the upregulation of α-Syn and the downregulation of tyrosine hydroxylase (TH), thereby alleviating dopaminergic neuron death in vitro in a PD model ( Geng et al, 2023 ).…”
Section: M6a and Parkinson’s Diseasementioning
confidence: 99%